Conscious mind, sleeping brain : perspectives on lucid dreaming - Gackenbach, Jayne; LaBerge, Stephen (My University, 1988)
A conscious mind in a sleeping brain: the title of this book provides a vivid image of the phenomenon of lucid dreaming, in which dreamers are consciously aware that they are dreaming while they seem to be soundly asleep. Lucid dreamers could be said to be awake to their inner worlds while they are asleep to the external world. Of the many questions that this singular phenomenon may raise, two are foremost: What is consciousness? And what is sleep? Although we cannot pro vide complete answers to either question here, we can at least explain the sense in which we are using the two terms. We say lucid dreamers are conscious because their subjective reports and behavior indicate that they are explicitly aware of the fact that they are asleep and dreaming; in other words, they are reflectively conscious of themselves. We say lucid dreamers are asleep primarily because they are not in sensory contact with the external world, and also because research shows physiological signs of what is conventionally considered REM sleep. The evidence presented in this book-preliminary as it is-still ought to make it clear that lucid dreaming is an experiential and physiological reality. Whether we should consider it a paradoxical form of sleep or a paradoxical form of waking or something else entirely, it seems too early to tell.
Keywords: Lucid dreams